DUKUNGAN TEMAN SEBAYA DENGAN PERILAKU KONSUMSI TABLET TAMBAH DARAH - Ulfa, Maria; Pratama, Kharisma; Khair, Fathul (Literasi Intelektual, 2025)
Background: Anemia is a condition characterized by hemoglobin levels below normal values based on age and gender. According to the West Kalimantan Health Department, the prevalence of anemia among adolescent girls increased from 18.3% in 2019 to 23.8% in 2020. Meanwhile, only 55.74% of adolescent girls in Pontianak received iron supplement tablets across 23 public health centers (Melyani, 2019). Objective: This study aimed to determine the relationship between peer support and the consumption behavior of iron supplement tablets among adolescent girls at SMAIT Al-Mumtaz Pontianak in 2024. Methods: This was an analytic observational study with a cross-sectional design. The population consisted of all female students in grades 10–12, with a total sample of 57 respondents selected through total sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test. Results: The findings showed that 43.9% of respondents received good peer support, while 56.1% received poor support. Regarding supplement consumption, 30 respondents (52.6%) demonstrated good behavior, and 27 respondents (47.4%) showed poor behavior. Statistical analysis revealed a significant relationship between peer support and supplement consumption behavior (p = 0.001). Conclusion: There is a significant relationship between peer support and the consumption behavior of iron supplement tablets among adolescent girls at SMAIT Al-Mumtaz Pontianak in 2024. Strengthening peer-based education and support programs may improve adherence to iron supplementation and help prevent anemia among adolescents.